The African Past in America as a Bakhtinian and Levinasian Other. "Rememory" as Solution in Toni Morrison's Beloved - ´Ángel Otero Blanco (Miscelánea: A Journal of English and American Studies)
A relational linguistic explanation of alterity and otherness in terms of reciprocity or interchangeability of subject and object positions constitutes the starting-point for an application of Levinas and Bakhtin's approaches to the theme of Time as other, to Toni Morrison's Beloved. The writer's neologism rememory implies physical and material designations which turn out to be con-fused with close-to-metaphysical claims about identity and coincidence. Consequently, the need, thirst or hunger, for a contingent and provisional sense of subjective and objective reality is reinforced by another re(a)lative distinction, to wit, the apparent opposition in the binomial presence/ absence, eventually amounting to the same. I also examine Levinas's metaphysical and common desire applied to beloved the character, storytelling as a way to enrich the characters' selves and the blues as a musical form that has evolved out of the African's terrible experience in America.